MARKET ECONOMY AS A PRECONDITION ESTABLISHMENT OWNERSHIP STRUCTURE IN SPORTS ORGANIZATIONS - Milica Radović; Ljiljana Fijat (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The first step in forming a market economy with privatization is necessary and radical changes in the institutional system. In the sport as well as any activities, privatization is a process of transformation of state ownership to private ownership in order to increase economic efficiency, utilization of available resources with the aim of encouraging economic development. The authors emphasize adoption as key institutional preconditions for the transformation of ownership in sports organizations, gives overview of various models of privatization in the surrounding countries. The aim of this paper is the analysis of potential problems, depending on the ownership structure, which is the result of the privatization process. Sports organizations should know in advance the advantages and disadvantages of different ownership structures, so that in the process of restructuring the chosen one that will ensure the realization of the priority goals.